Analyzing the CDR3 Repertoire with respect to TCR—Beta Chain V-D-J and V-J Rearrangements in Peripheral T Cells using HTS - Ma, Long (Sci Rep, 2016)
V-D-J rearrangement of the TCR—beta chain follows the 12/23 rule and the beyond 12/23 restriction. Currently, the proportion and characteristics of TCR—beta chain V—J rearrangement is unclear. We used high-throughput sequencing to compare and analyze TCR—beta chain V-J rearrangement and V-D-J rearrangement in the CDR3 repertoires of T cells from the PBMCs of six volunteers and six BALB/c mice. The results showed that the percentage of V-J rearrangement of the volunteers was approximately 0.7%, whereas that of the mice was 2.2%. The clonality of mice V-J rearrangement was significantly reduced compared with the V-D-J rearrangement, whereas the clonality of human V-J rearrangement was slightly reduced compared with the V-D-J rearrangement. V-J rearrangement in CDR3 involved the significant usage of N, S, F and L, whereas V-D-J rearrangement in CDR3 involved the significant usage of R and G. The levels of V deletion and J deletion in V-J rearrangement were significantly reduced compared with V-D-J rearrangement. TRBD and TRBJ usage in V-J rearrangement differed from that of V-D-J rearrangement, including dominant usage of TRBV and TRBJ and their pairing. Taken together, these results provide new ideas and technology for studies of V-D-J rearrangement and V-J rearrangement in the CDR3 repertoire.